Determining the structure of dark-matter couplings at the LHC - Haisch, U; Hibbs, A; Re, E (2014)
The latest LHC monojet searches place stringent bounds on the pp→χ̄χ cross section of dark matter. Further properties such as the dark matter mass or the precise structure of the interactions between dark matter and the standard model, however, cannot be determined in this manner. We point out that measurements of the azimuthal angle correlations between the two jets in 2j+χ̄χ events may be used to disentangle whether dark matter pair production proceeds dominantly through tree or loop diagrams. Our general observation is illustrated by considering theories in which dark matter interacts predominantly with the top quark. We show explicitly that in this case the jet-jet azimuthal angle difference is a gold-plated observable to probe the Lorentz structure of the couplings of dark matter to top quarks, thus testing the CP nature of the particle mediating these interactions. © 2014 American Physical Society.